1991
DOI: 10.1099/00207713-41-1-88
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Campylobacter, Helicobacter, and Wolinella Taxonomy: Emendation of Generic Descriptions and Proposal of Arcobacter gen. nov.

Abstract: Hybridization experiments were carried out between DNAs from more than 70 strains of Campylobacter spp. and related taxa and either 3H-labeled 23s rRNAs from reference strains belonging to Campylobacter fetus, Campylobacter concisus, Campylobacter sputorum, Campylobacter coli, and Campylobacter nitrofigilis, an unnamed Campylobacter sp. strain, and a Wolinella succinogenes strain or 3H-or 14C-labeled 23s rRNAs from 13 gram-negative reference strains. An immunotyping analysis of 130 antigens versus 34 antisera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
355
2
20

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 677 publications
(387 citation statements)
references
References 42 publications
10
355
2
20
Order By: Relevance
“…Further, the three Campylobacter groups had a 49.3% overall 16S rRNA sequence similarity to representatives of the alpha, beta, and gamma phylogenetic branches of the class Proteobacteria, a depth of divergence greater than that among the three branches themselves and consistent with the conclusions reached by Romaniuk et al (50). Stackebrandt et al (54) took the position that overall there was a meaningful affinity between the campylobacters and members of the class Proteobacteria, and Vandamme et al (61,62) concluded that while the campylobacters clearly constitute a sixth rRNA superfamily within the gram-negative bacteria and are equally removed from all subclasses within the class Proteobacteria, it seems appropriate to consider rRNA superfamily Vl a fifth subclass of the class Proteobacteria, as deduced from a suggestion of Murray et al (33).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Further, the three Campylobacter groups had a 49.3% overall 16S rRNA sequence similarity to representatives of the alpha, beta, and gamma phylogenetic branches of the class Proteobacteria, a depth of divergence greater than that among the three branches themselves and consistent with the conclusions reached by Romaniuk et al (50). Stackebrandt et al (54) took the position that overall there was a meaningful affinity between the campylobacters and members of the class Proteobacteria, and Vandamme et al (61,62) concluded that while the campylobacters clearly constitute a sixth rRNA superfamily within the gram-negative bacteria and are equally removed from all subclasses within the class Proteobacteria, it seems appropriate to consider rRNA superfamily Vl a fifth subclass of the class Proteobacteria, as deduced from a suggestion of Murray et al (33).…”
Section: Discussionsupporting
confidence: 72%
“…This group includes Campylobacter, Arcobacter, Helicobacter, Wolinella, and "Flexispira" spp. and has been argued to constitute a separate bacterial lineage within the class Proteobacteria (62,63). The most recently published phylogenetic tree based on small-subunit rRNA sequences has the group positioned in the delta and epsilon subdivisions of the Proteobacteria (purple bacteria) (39).…”
mentioning
confidence: 99%
“…Dechloromonas degrades benzene, toluene, ethylbenzene, and xylene (Chakraborty et al, 2005). Some bacteria detected at the Liulin site might function in the cycling of nitrogen, e.g., Arcobacter has been reported to reduce nitrate and fix nitrogen (Vandamme et al, 1991), Azonexus was described as being denitrifying bacteria (Quan et al, 2006) and as harbouring the nitrogenase gene nifH and able to reduce nitrate (Chou et al, 2008). As all of the metabolic functions above were inferred from DNA sequences and several were inferred from aerobically incubation, further determination of the activities and function of these bacteria using stable-isotope probing (SIP) and anaerobic cultivation is needed in future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomy of this group of organisms is now being clarified. Recent phylogenetic work has resulted in the creation of the genus Helicobacter, and new species of this genus are rapidly being recognized (14, 17,32,33,36,40,43). Although three of the gastric helicobacters are very similar physiologically and show high degrees of similarity (96%) in their 16s rRNA sequences, these bacteria have very different morphologies (19,24,31).…”
mentioning
confidence: 99%